2017
DOI: 10.1097/pts.0000000000000379
|View full text |Cite
|
Sign up to set email alerts
|

Description and Yield of Current Quality and Safety Review in Selected US Academic Emergency Departments

Abstract: Objectives Quality and safety review for performance improvement is important for systems of care and is required for US academic emergency departments (EDs). Assessment of the impact of patient safety initiatives in the context of increasing burdens of quality measurement compels standardized, meaningful, high-yield approaches for performance review. Limited data describe how quality and safety reviews are currently conducted and how well they perform in detecting patient harm and areas for improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…These are poor indicators of quality and safety, rarely identifying AEs, with yields (AEs detected/records reviewed) under 2%. [6][7][8][9][10][11] Event reporting systems are also commonly used but may miss~90% of AEs, 12 and up to 95% of reported events do not involve patient harm. 13 These approaches are decades old, inefficient, and likely underestimate patient harm, 9 increasing the likelihood that AEs go undiscovered, unreported, and thus unaddressed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These are poor indicators of quality and safety, rarely identifying AEs, with yields (AEs detected/records reviewed) under 2%. [6][7][8][9][10][11] Event reporting systems are also commonly used but may miss~90% of AEs, 12 and up to 95% of reported events do not involve patient harm. 13 These approaches are decades old, inefficient, and likely underestimate patient harm, 9 increasing the likelihood that AEs go undiscovered, unreported, and thus unaddressed.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11] Event reporting systems are also commonly used but may miss~90% of AEs, 12 and up to 95% of reported events do not involve patient harm. 13 These approaches are decades old, inefficient, and likely underestimate patient harm, 9 increasing the likelihood that AEs go undiscovered, unreported, and thus unaddressed. 9,14,15 New, efficient methods for AE detection and measurement are needed.…”
mentioning
confidence: 99%
“…Accordingly, for years, overall approaches to surveillance have remained fairly static, focusing on periodic reviews of specific case types: returns with admission, deaths, upgrades in care, etc., with a low yield for identifying AEs. 1,23 Referrals from other physicians, administrators, or departments is the only category that we have consistently found to be high-yield. 1,24 Trigger tool studies have demonstrated a 10-fold increase in AE detection compared to traditional methods, 2 with AE rates of up to 27-33% of hospital or skilled nursing facilities admissions respectively, 3,4 and estimates of deaths from AEs 2-4 times higher than previously thought.…”
Section: Discussionmentioning
confidence: 65%
“…1,23 Referrals from other physicians, administrators, or departments is the only category that we have consistently found to be high-yield. 1,24 Trigger tool studies have demonstrated a 10-fold increase in AE detection compared to traditional methods, 2 with AE rates of up to 27-33% of hospital or skilled nursing facilities admissions respectively, 3,4 and estimates of deaths from AEs 2-4 times higher than previously thought. 6 Because ED encounters are significantly shorter than inpatient stays, with limited "exposure time" to the system, we (fortunately) do not expect to see these same AE rates.…”
Section: Discussionmentioning
confidence: 65%
“…AEs may occur in up to 27.8% of ED visits, but estimates are based on limited data, often confined to specific AE types (e.g., adverse drug events) or subpopulations (e.g., asthma, boarding patients) . Commonly used approaches to identify AEs in the ED have a yield of just under 2%, likely underestimating the true burden of AEs and reflecting inadequate surveillance . Newer methods, such as the IHI's Global Trigger Tool (GTT), have been developed for a variety of clinical settings and demonstrate substantially higher yields compared to traditional approaches .…”
mentioning
confidence: 99%